Newly Found Peacekeeper: Potential of CD8+ Tregs for Graft-Versus-Host Disease - Wang, Weihao; Hong, Tao; Wang, Xiaoqi; Wang, Rui; Du, Yuxuan; Gao, Qiangguo; Yang, Shijie; Zhang, Xi (Frontiers in Immunology, 2021)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains the most effective and potentially curative treatment for a variety of hematologic malignancies. However, graft-versus-host disease (GVHD) is a major obstacle that limits wide application of allo-HSCT, despite the development of prophylactic strategies. Owing to experimental and clinical advances in the field, GVHD is characterized by disruption of the balance between effector and regulatory immune cells, resulting in higher inflammatory cytokine levels. A reduction in regulatory T cells (Tregs) has been associated with limiting recalibration of inflammatory overaction and maintaining immune tolerance. Moreover, accumulating evidence suggests that immunoregulation may be useful for preventing GVHD. As opposed to CD4+ Tregs, the CD8+ Tregs population, which constitutes an important proportion of all Tregs, efficiently attenuates GVHD while sparing graft-versus-leukemic (GVL) effects. CD8+ Tregs may provide another form of cellular therapy for preventing GVHD and preserving GVL effects, and understanding the underlying mechanisms that different from those of CD4+ Tregs is significant. In this review, we summarize preclinical experiments that have demonstrated the role of CD8+ Tregs during GVHD and attempted to obtain optimized CD8+ Tregs. Notably, although optimized CD8+ Tregs have obvious advantages, more exploration is needed to determine how to apply them in the clinic.